If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -3 = 7x + -1 Reorder the terms: -3 + 3x = 7x + -1 Reorder the terms: -3 + 3x = -1 + 7x Solving -3 + 3x = -1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -3 + 3x + -7x = -1 + 7x + -7x Combine like terms: 3x + -7x = -4x -3 + -4x = -1 + 7x + -7x Combine like terms: 7x + -7x = 0 -3 + -4x = -1 + 0 -3 + -4x = -1 Add '3' to each side of the equation. -3 + 3 + -4x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = -1 + 3 -4x = -1 + 3 Combine like terms: -1 + 3 = 2 -4x = 2 Divide each side by '-4'. x = -0.5 Simplifying x = -0.5
| 25x^2-45-10=0 | | 6x^7=11x^6 | | 13c+4ab-9b+2ab+-17b= | | 6+2c+3=7+c | | 13k^2+26k+13= | | X(x-2a)+a^2+1=0 | | w^6+8w^3+7=0 | | d^6+2d^3-80=0 | | 9a+26c+2ab+13c+4ab-9b= | | -14y=7x+1 | | 12a^3b^2-27ab^2=0 | | 4(1-x)+7x=4 | | 18x^3-27x^2-2x+3=0 | | a^3b^3+64=0 | | 5x+3(2x-9)=17 | | 30y^3+12y^2+5y+1=0 | | =126 | | 5(3a+5b)= | | 24c^2-24c+6=0 | | (3x-1)(2x+4)-(3x-1)(x+1)=(3x-1)(2x-3) | | 1.5x+4=1 | | 10n=9n+5 | | -3(m-2)+6m=9(m-1) | | -8b+b+13ab= | | 2kx-2ky-12=0 | | x^3-15x^2-5x-52=0 | | 5x-1=3(2x+4) | | 2ad-9b+-8b= | | 5x=19+y | | -[8z-(11z+4)]=4+(2z+0) | | 4x^2-x+4=04 | | 2(x+3)+3x=51 |